Understanding riddles by the type of "Description of signs" by second grade students with general speech underdevelopment (level III) - Blagikh N. E. (Modern educational process: psychological and pedagogical support, educational strategies, 2024)
The article describes the difficulties of guessing riddles by the type of "Description of signs" in second grade students with ONR (III level of speech development). The answers and their causes are given. The children give the presented answers after listening to the riddle holistically, without additional types of help. The reasons for such responses can serve as a basis for determining the areas of work and types of assistance in order to expand knowledge and ideas about the surrounding reality among students of the second grades with ONR (III level of speech development).
Keywords: общее недоразвитие речи; загадки; III уровень; riddles; учащиеся 2 классов; general underdevelopment of speech (level III); 2nd grade students